(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Integrative Criminology and the Noological Dimension As criminologist Gregg Barak argued, integrative criminology means different things to different criminologists. Viewed comprehensively, the multiple strengths of investigations, examinations and incorporations constitute integrative criminology. The same researcher considers that informal and formal integration currently consists of the convergence of at least three recent theoretical forces within the criminological enterprise: the „development”, „life course” and „reciprocal” theories of human behavior. All these theories have common integrative approaches to the individual problem of relating the environment and how these experiences establish paths to and / or away from antisocial behavior, deviance, delinquency, crime or violence. We believe and try to argue that this triad of integrative criminological theories is an open system that must be linked to the „noological model” of social interaction, originally created by Ilie Badescu, a Romanian sociologist, in a comprehensive monograph entitled Noological Sociology. The spiritual order of society. We consider that between these two types of approach there is harmony, complementarity and completeness,and the noological approach is able to multiply the integrative capacity ofthe criminological vision.